The peroxisomal disorder spectrum and Heimler syndrome: Deep phenotyping and review of the literature. Issue 3 (31st August 2020) - Varela, Malena Daich; Jani, Priyam; Zein, Wadih M.; D'Souza, Precilla; Wolfe, Lynne; Chisholm, Jennifer; Zalewski, Christopher; Adams, David; Warner, Blake M.; Huryn, Laryssa A.; Hufnagel, Robert B.
Abstract: The spectrum of peroxisomal disorders is wide and comprises individuals that die in the first year of life, as well as people with sensorineural hearing loss, retinal dystrophy and amelogenesis imperfecta. In this article, we describe three patients; two diagnosed with Heimler syndrome and a third one with a mild‐intermediate phenotype. We arrived at these diagnoses by conducting complete ophthalmic (National Eye Institute), auditory (National Institute of Deafness and Other Communication Disorders), and dental (National Institute of Dental and Craniofacial Research) evaluations, as well as laboratory and genetic testing. Retinal degeneration with macular cystic changes, amelogenesis imperfecta, and sensorineural hearing loss were features shared by the three patients. Patients A and C had pathogenic variants in PEX1 and Patient B, in PEX6 . Besides analyzing these cases, we review the literature regarding mild peroxisomal disorders, their pathophysiology, genetics, differential diagnosis, diagnostic methods, and management. We suggest that peroxisomal disorders are considered in every child with sensorineural hearing loss and retinal degeneration. These patients should have a dental evaluation to rule out amelogenesis imperfecta as well as audiologic examination and laboratory testing including peroxisomal biomarkers and genetic testing. Appropriate diagnosis can lead to better genetic counseling and management of the associated comorbidities.